Clinical Management of Syncope in Emergency Department Based on Risk Stratification : A Review Literature - Putri Annisa Kamila; Ardian Rizal; Novi Kurnianingsih; Sasmojo Widito (Heart Science Journal, 2020)
Background: Background Syncope is a frequent problem among patients who present to the ED, accounts for 3% of emergency department admission and 1% of hospitalization. It is characterized by a comparatively short and self-limited loss of consciousness, which is caused by temporary cerebral hypoperfusion.Objective: Therefore, Risk stratification performed in the ED can guide triage decisions, and Risk-stratifying patients into low, moderate, and high-risk groups can assist medical decisions and determine the patient’s disposition.Discussion: The central point of syncope progression pathophysiology is the reduction of systemic blood pressure (BP) with a drop in global cerebral blood flow. Based on the European Society of Cardiology (ESC) syncope practice guidelines, syncope is classified into three categories, Neurally-mediated syncope (neural reflex syncope), Orthostatic hypotension, Cardiac syncope. Proper evaluation of syncope cases could in turn enable timely hospitalization and treatment by syncope experts. Assessment of a patient with syncope can be difficult, requiring a wide variety of medical testing with high health care costs. Sometimes, even after a careful examina- tion, it may not be possible to determine a definitive etiology for syncope. Given these uncertainties, about one-third of emergency room (ER) syncope/collapse patients are referred for assessment to the hospital, including non to low-risk patients. establish the urgency of any further work-up.Conclusion: Syncope assessment and treatment are very difficult, and syncope cases should be treated and dispositioned properly using proper risk stratification guidelines.